Iatrogenic cyanosis in children, a pitfall of atrial septal defect repair - Hassan Mottaghi; Mahdi Kahrom (Journal of Cardio-Thoracic Medicine, 2020)
AbstractToday surgical repair of the atrial septal defect (ASD) is considered as relatively a simple and safe procedure with minor to no morbidity and mortality. When a complication occurs after ASD repair, is associated with considerable morbidity and mortality, which is much higher than primary surgical procedure. We report two patients that underwent ASD repair with caval inflow occlusion without CPB with late presentations of iatrogenic diversion of IVC to LA and subsequent complications of right to left shunting.